Left ventricular diastolic dyssynchrony in patients with treatment-naive hypertension and the effects of antihypertensive therapy. Issue 2 (February 2015) - Kwon, Beom-June; Lee, Su-Hyun; Park, Chan-Suk; Kim, Dong-Bin; Park, Hun-Jun; Jang, Sung-Won; Ihm, Sang-Hyun; Youn, Ho-Joong; Seung, Ki-Bae; Kim, Hee-Yeol
<x xml:space="preserve">Abstract</x> Aims: The presence of left ventricular diastolic dyssynchrony is well known to be a frequent and important manifestation in heart failure. We investigated diastolic dyssynchrony in patients with treatment-naive hypertension, compared with normal controls; the determinants of the presence of diastolic dyssynchrony by performing comprehensive studies including laboratory, arterial stiffness, central blood pressure (BP), ambulatory BP monitoring (ABPM), and transthoracic echocardiography (TTE) evaluations; the effects of 6-month antihypertensive therapy on diastolic dyssynchrony; and the predictors associated with the change of diastolic dyssynchrony after medical therapy. Methods: A total of 325 treatment-naive hypertensive patients and 172 normal controls were prospectively enrolled. Hypertensive patients were followed up at 6 months after medical therapy, and were assessed by serial TTE (at baseline and 6-month follow-up visit) and clinical evaluations. The time-to-peak myocardial early diastolic velocity (Te) of the 12 left ventricular segments was measured with reference to the QRS complex. The standard deviation (SD) of Te of all 12 left ventricular segments (Te-SD12) and the maximal difference in Te between any two of the 12 left ventricular segments (Te-Max) were calculated. A Te-SD12 at least 34 or Te-Max at least 113 ms was regarded as indicating the presence of diastolic dyssynchrony. Results: Diastolic dyssynchrony was more prevalent in treatment-naive hypertensive patients, compared with normal controls (15.4 versus 7.0%, P = 0.007). Male sex [odds ratio (OR), 9.36 (1.93–45.41)], magnesium [OR per 1 SD, 2.54 (1.32–4.90)], night-time heart rate [HR; OR per 1 SD, 2.44 (1.18–5.05)], and mitral E/A [OR per 1 SD, 0.13 (0.04–0.45)] were independent determinants for the diastolic dyssynchrony in hypertensive patients. A 6-month follow-up, echocardiography was performed in 74 of 275 patients without diastolic dyssynchrony (group 1) and 26 of 50 patients with diastolic dyssynchrony (group 2). Diastolic dyssynchrony (Te-SD12, Δ = −8.3 ms; Te-Max, Δ = −27.6 ms; prevalence, Δ = −42.3%; all P < 0.05) improved in group 2, whereas it did not in group 1. Baseline daytime HR (P = 0.008) and magnesium levels (P = 0.029) and changes of the midwall fractional shortening (P = 0.026), mitral E/A (P = 0.003), mean annulus Ea (P = 0.003), mean annulus Ea/Aa (P = 0.020), and mitral peak E (P = 0.042) were independent predictors for changes of Te-SD12. Conclusion: Diastolic dyssynchrony is not rare in treatment-naive hypertensive patients. Male sex, magnesium levels, night-time HR, and mitral E/A are independent determinants for the impaired diastolic dyssynchrony. Antihypertensive therapy reduces both the severity and prevalence of diastolic dyssynchrony in patients with impaired diastolic dyssynchrony. Daytime HR, magnesium levels, and indications of systolic or diastolic dysfunction are independent predictors for improvements in diastolic dyssynchrony. Thus, magnesium levels, HR, and diastolic dysfunction seem to have important implications for diastolic dyssynchrony in hypertensive patients, whereas left ventricular hypertrophy, office BPs, arterial stiffness, central BPs, and ABPM parameters do not.